Apramycin kills replicating and non-replicating Mycobacterium tuberculosis - Kaur, Parvinder; V. K., Ramya; C. N., Naveenkumar; K., Bharathkumar; Singh, Mayas; Hobbie, Sven N.; Shandil, Radha Krishan; Narayanan, Shridhar (Frontiers in Tropical Diseases, 2024)
IntroductionMycobacterium tuberculosis (Mtb) has the capability to dodge the immune system by escaping into alternate physiological forms by forming drug tolerant populations under the immune pressure in the host. New drugs are urgently needed to treat these non-replicating persisters. In the past, aminoglycoside antibiotics have played a pivotal role in TB chemotherapy.MethodsHere, we explored the therapeutic potential of a monosubstituted deoxystreptamine aminoglycoside, apramycin (APR) which is different in its chemical structure from the other clinically relevant aminoglycoside antibiotics that are all disubstituted, e.g., amikacin (AMI). We determined the APR MIC as 0.25-1 µg/ml for sensitive and multidrug-resistant Mtb (MDRTB), including amikacin (AMI) resistant strains.ResultsIn standard time-kill kinetic assays, the bactericidal activity of APR was similar to that of AMI demonstrating dose-dependent killing of planktonic Mtb. However, in biofilm and macrophage intracellular killing assays, APR appeared significantly more potent than AMI. Further, APR monotherapy was efficacious in a mouse chronic TB lung infection model ( 0.92 log10 CFU/lung reduction). APR combination therapy with the current 1st line standard of care (SoC) antibiotic combination of isoniazid (H), rifampicin (R), ethambutol (E), and pyrazinamide (Z) was found to be additive (HREZ=1.88 vs. HREZ-APR=2.78 log10CFU/lung reduction).DiscussionThe results indicate the potential of apramycin-based combinations for the treatment of human tuberculosis.